Violência sexual e rede de atendimento: o olhar dos profissionais do CREAS - Paixão, Gláucia Pereira da (2011)
This investigation analyzes the perspective of professionals in the Reference Centre for Social Welfare-CREAS of João Pessoa- PB about the demands of children and adolescents who experienced sexual abuse, the family reaction and the service from institutions to relative to ensure your rights. This survey also the implications of actions taken by the family of these individuals and by institutions of the coping network in which they were received. It was used as a theoretical framework, some tool of socio-historical approach of Vygotsky: references pertaining to the rights of children and adolescents, and to social policies to address violence against children and adolescents. As methodological procedures, there were individual semi-structured interviews with professionals of CREAS. The sample consisted eight participants and the interviews were transcribed and analyzed through the content analysis of Bardin. The data reveal that, according to participants, the source of demand of children and adolescents who go to CREAS, comes from the Justice system, from the system of repression, from school and spontaneous demand. When children, adolescents and their families come to CREAS, the participants reported that they take care of parent, child and adolescent, articulate with other institutions and support the family. When sexual abuse is revealed, these individuals receive help from family, friends and professionals. Among the family members who help, the mother stands. When they become aware of the abuse experienced by children, some families take protective actions, others do not offer support and exclude children and adolescents in the home. In view of the professionals interviewed, only some children have demands about the family. When they do, complain that they wanted the mother had believed in them, they wanted the mother had left behind her partner, they wanted her mother had not left them alone with the father, and others are passive on the actions of the family. After the revelation of the abuse, the participants indicated that some families seek professional support, taking children and adolescents to Guardian Council, the Police, the CREAS and the Hospital and the service of these institutions is evaluated by the participants, sometimes as appropriate, others as inappropriate. The participants notice that children and adolescents elaborate demands about the service, they wanted the actions taken were faster, punishment of the perpetrator and a more careful service. According to participants, these individuals do not like the service provided by some institutions, but CREAS was referred as the best place in which they were received, for according to participants, offers a more humane and careful treatment. The participants also reveal that children and adolescents have demands linked to the situation of sexual abuse experienced and want a better life. The emergence of these demands shows that, although they are presented, they are not being satisfied by family and by professionals of coping network to combat sexual violence. It is emphasized that families and professionals comply with some recommendations and provisions regarding the rights of children and adolescents, sometimes not. Before that, the guarantee of rights and the meeting the demands of children and adolescents are being insufficient, which might be consider as risk factors for development of these children and adolescents, bringing them implications for physical, social and emotional development.